Functions of Agrarian Families in the Prevention of Stunting: A Literature Review - Wariin, Sulton; Susanto, Tantut; Rahmawati, Iis (STIKep PPNI Jawa Barat, 2024)
Aims: This research aims to identify factors related to the functions of agrarian families in rural areas that can contribute to the prevention of stunting. Methods: This study employs a literature review design with keywords